Parental Incarceration and Social Status Attainment of Hispanic Young Adults - Ryabov, Igor (Crime & delinquency, 2020)
The fact that parental incarceration has become a common event in the life course of many children is troubling. Using structural equation modeling, the present study investigates how immigrant generational status and family socioeconomic background interact with parental incarceration to influence status attainment for Hispanic young adults. Three indicators of status attainment in young adulthood are used as outcome variables—educational attainment, wage, and job quality. Results indicate that parental incarceration has a strong and negative influence on all three indicators of attained status. Most importantly, we found that parental incarceration mediates influence of immigrant generational status and family socioeconomic background on status attainment of Hispanic young adults.